Campaigns to reduce mental illness stigma in Europe: a scoping review - Borschmann, R.; Greenberg, N.; Jones, N.; Henderson, R. C. (Die Psychiatrie, 2014)
Background: Evidence has emerged in recent decades about effective and ineffective methods to reduce mental illness related stigma and discrimination. As more European countries start national anti-stigma campaigns, there is potentially more to learn from their experiences, but also a risk that, with such rapid developments, lessons may be missed.Aim: This scoping review aims to identify and discuss European stigma reduction campaigns conducted to date.Methods: We searched electronic databases, hand-searched reference lists of identified articles and contacted stigma experts to enquire about ongoing initiatives.Results: We identified anti-stigma campaigns in 21 European countries and regions. We found considerable variation in their content, delivery formats, duration and target groups.Conclusions: Although anti-stigma campaigns have been implemented in many European countries, the level of attention paid to sharing lessons learned is variable. It is vital that campaigns are evaluated, to maximise their potential impact both on the target population, and that the findings are disseminated widely to allow international learning.
Keywords: Stigma; discrimination; mental health; Europe; intervention; campaign; Open The Doors